Short-term outcomes of drug-coated balloon versus drug-eluting stent for de novo saphenous vein graft lesions in coronary heart disease - Lin, Li; Lu, Wenjie; Wang, Xi; Pan, Liang; Wang, Xule; Zheng, Xiaolin; Li, Ran; Shan, Yingguang; Peng, Meng; Qiu, Chunguang (Frontiers in Cardiovascular Medicine, 2023)
Background As a device for percutaneous coronary intervention, drug-coated balloon (DCB) is widely used to treat in-stent restenosis. However, data regarding the use of DCB in treating de novo saphenous vein graft (SVG) lesions are limited. This study aimed to explore the outcomes of using the DCB in the treatment of de novo SVG lesions of coronary heart disease (CHD). Methods This retrospective and observational study analyzed CHD patients with de novo SVG lesions treated with DCB or the new-generation drug-eluting stent (DES) between January 2018 and December 2020. Restenosis was the primary endpoint, whereas target lesion revascularization (TLR), major adverse cardiac events, restenosis, cardiac death, target vessel revascularization, and myocardial infarction were the secondary outcomes. Results We enrolled 31 and 23 patients treated with DCB and DES, respectively. The baseline clinical data, lesion characteristics, and procedural characteristics were similar between the two groups. Twenty-eight (90.3%) patients in the DCB group and 21 (91.3%) in the DES group completed follow-up angiography after 1 year. The quantitative coronary angiography measurements at angiographic follow-up showing late lumen loss were −0.07 ± 0.95 mm for the DCB group and 0.86 ± 0.71 mm for the DES group (P = 0.039), and the rates of restenosis were 13.3% and 21.7% for the DCB and DES groups, respectively (P = 0.470). No significant differences were observed in the rates of MACE (16.7% vs. 26.1%, P = 0.402) and TLR (13.3% vs. 4.3%, P = 0.374) during clinical follow-up. Conclusion Our findings suggest that when pre-dilatation was successful, DCB might be safe and effective in treating de novo SVG lesions.